Earthquake Disaster Simulation of Civil Infrastructures From Tall Buildings to Urban Areas - Lu, Xinzheng; Guan, Hong.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
The first edition of this monograph, presenting accurate and efficient simulations of seismic damage to buildings and cities, has received significant attention from the research community. To keep abreast of the rapid development in recent years, our latest breakthrough achievements have been added to this new edition, including novel resilient structural components, secondary disaster simulations, emergency responses and resilient recovery of communities after earthquake. This edition comprehensively covers a range of numerical modeling approaches, higher performance computation methods, and high fidelity visualization techniques for earthquake disaster simulation of tall buildings and urban areas. It also demonstrates successful engineering applications of the proposed methodologies to typical landmark projects (e.g., Shanghai Tower and CITIC Tower, two of the world's tallest buildings; Beijing CBD and San Francisco Bay Area). Reported in this edition are a collection of about 60 high impact journal publications which have already received high citations.
Introduction -- High fidelity Computational Models for Earthquake Disaster Simulation of Tall Buildings.-Earthquake Disaster Simulation of Typical Supertall Buildings -- Comparison of Seismic Design and Resilience of Tall Buildings based on Chinese and US Design Codes -- Simplified Models for Earthquake Disaster Simulation of Supertall Buildings -- Seismic Resilient Outriggers and Multi-hazard Resilient Frames -- Building Models for City-scale Nonlinear Time-history Analyses -- Regional Seismic Loss Estimation of Buildings -- Visualization and High-performance Computing for City-scale Nonlinear Time-history Analyses -- Fire Following Earthquake and Falling Debris Hazards -- Emergency Response and Post-earthquake Recovery using City-scale Nonlinear Time-history Analysis -- Earthquake Disaster Simulation of Typical Urban Areas -- Conclusions.
Keywords: Civil engineering; Buildings$1 (BDesign and construction.s; Natural disasters; Civil Engineering; Building Construction and Design; Natural Hazards